Laparoscopic Puestow procedure for chronic pancreatitis in children - Apurva Arora; Prakash Agarwal; Rajkishore Bagdi; Madhu Ramasundaram; M L Sankar Narayanan (Wolters Kluwer Medknow Publications, 2020)
Chronic pancreatitis (CP) is a sequelae characterized by recurrent attacks of pancreatitis leading on to fibrosis and calcification of both ductal and parenchymal elements of the pancreas. Most of these, if left untreated at the right time, will lead on to burnt-out pancreas with complete atrophy of the parenchyma, leading on to endocrine/exocrine insufficiency. The pain in such patients is most likely due to ductal hypertension, parenchymal hypertension, and head mass causing perineural inflammation. Puestow procedure (longitudinal pancreaticojejunostomy) is the surgery of choice in selected patients with ductal hypertension where decompression of the duct provides symptomatic relief. Performance of such procedures in children by minimal access laparoscopic method is still evolving. We report a series of three patients (aged 10, 12, and 16 years) diagnosed with CP and successfully managed by laparoscopic Puestow procedure.